PERSONALITIES OF THE MAIN CHARACTER IN DILAN DIA ADALAH DILANKU TAHUN 1990 NOVEL BY PIDI BAIQ - Christye Farikha Pasaribu; Hidayati Hidayati; Bima Prana Chitra (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This thesis discusses the personality structure of the main character in Dilan Dia Adalah Dilanku Tahun 1990 novel. The personality structures in question are id, ego, and superego. The data for this research is the Dilan Dia Adalah Dilanku Tahun 1990 novel which was collected using the literature study method. Data analysis methods used are formal methods and content analysis. The basis for implementing the content analysis method is interpretation. The results of data analysis are presented using a qualitative descriptive method. The theory used to describe the personality structure of the main character is Sigmund Freud's psychoanalytic theory which includes the Id, Ego, and Superego. The results of this study reveal the personality form of the id ego superego of the main character, Milea. The form of id in the main character is to refuse discomfort, seek pleasure and fulfill biological needs. The main character's ego is the morality of humanity in the form of an ego defense mechanism in problem solving and decision making. The form of the main character's superego is the superego holding back the fullness of the id because Milea's anxiety over things that haven't happened yet causes doubts which then creates an ego. Keywords: Psychoanalysis, personality structure, id, ego, superego